2010
DOI: 10.4070/kcj.2010.40.11.565
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Triggering Activities and the Circadian Distribution of Acute Aortic Dissection

Abstract: Background and ObjectivesThere are limited data examining triggering activities and circadian distribution at the onset of acute aortic dissection (AAD) in the context of diagnostic and anatomical classification. The aim of this study was to further investigate this relationship between triggering activities and circadian distribution at the onset of AAD according to diagnostic and anatomic classification.Subjects and MethodsA total of 166 patients with AAD admitted to Kyungpook National University Hospital be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…One of the different findings of this study was a peak of AAD occurrence on Wednesday in both centers. Although Lasica and associates 20 and Ryu and associates 21 also reported a Wednesday peak, most literature documented a peak of dissection onset on Monday. 5,8,22,23 The Monday peak was ascribed to the emotional stress of starting weekly work activities, 24 less favorable biochemical factors (such as carbohydrate and lipid levels), 25 and higher blood pressure levels 26 on Monday compared with other days of the week.…”
Section: Commentmentioning
confidence: 99%
“…One of the different findings of this study was a peak of AAD occurrence on Wednesday in both centers. Although Lasica and associates 20 and Ryu and associates 21 also reported a Wednesday peak, most literature documented a peak of dissection onset on Monday. 5,8,22,23 The Monday peak was ascribed to the emotional stress of starting weekly work activities, 24 less favorable biochemical factors (such as carbohydrate and lipid levels), 25 and higher blood pressure levels 26 on Monday compared with other days of the week.…”
Section: Commentmentioning
confidence: 99%
“…Other hemodynamic factors would include underlying chronic hypertension, acute hypertensive episodes as well as other extrinsic events. Ryu et al [9], in their small series of 166 patients with STADs, found that 72% of the STAD episodes were associated with either physical (53%) or mental (19%) activities. Hatzaras et al [10] documented 31 patients with an acute STAD associated with intense physical exertion, predominantly weightlifting.…”
Section: Resultsmentioning
confidence: 99%